THE STUDY OF STUDENTS’ DIFFICULTIES IN MASTERING THE CONCEPT OF ARCHIMEDES’ PRINCIPLE - Tsania Nur Diyana; Sutopo Sutopo; Dwi Haryoto (Pendidikan Kimia Unimus, 2020)
The focus of this study is to determine students' difficulties related to mastering the concept of Archimedes Principles topics. The study used descriptive quantitative method with the subject 35 XIth students. The research instrument was 10 multiple choice questions about Archimedes principle. Although there are improvements, but overall students do not fully understand the concept of the Archimedes principle. Difficulties among students are failing to understand that the buoyancy force is the resultant force by fluid pressure on the object and still considers the immersed object to have the Archimedes force affected by the depth of the object. When working on the application of the problem the students managed to answer correctly, but when completing the formulation questions the students were still get difficulties